FIM job specialization / Farah Amira Abdul Rahim, Nur Ashiqin Zolkifli and Tuan Safa'at Tuan Ameri - Abdul Rahim, Farah Amira; Zolkifli, Nur Ashiqin; Tuan Ameri, Tuan Safa'at (Faculty of Information Management, 2014)
Faculty of Information Management (FIM), UiTM, takes pride in being the pioneer in providing professional education to fulfill manpower needed by the country in four important fields name as Library Management, Records Management, Resource Center Management and Information System Management. FIM academics programs, supplemented by industry attachments, equip graduates with knowledge and skills to take in the challenging demands of managing information in various forms and types of organizations. Besides, this article will cover on job specialization to the FIM graduates based on those four important fields.